Emergent B2 chemical orderings in the AlTiVNb and AlTiCrMo refractory high-entropy superalloys studied via first-principles theory and atomistic modelling - Christopher D Woodgate; Hubert J Naguszewski; David Redka; Ján Minár; David Quigley; Julie B Staunton (JPhys Materials)
We study the thermodynamics and phase stability of the AlTiVNb and AlTiCrMo refractory high-entropy superalloys using a combination of ab initio electronic structure theory—namely a concentration wave analysis—and atomistic Monte Carlo simulations. Our multiscale approach is suitable both for examining atomic short-range order in the solid solution, as well as for studying the emergence of long-range crystallographic order with decreasing temperature. In both alloys considered in this work, in alignment with experimental observations, we predict a B2 (CsCl) chemical ordering emerging at high temperatures, which is driven primarily by Al and Ti, with other elements expressing weaker site preferences. The predicted B2 ordering temperature for AlTiVNb is higher than that for AlTiCrMo. These chemical orderings are discussed in terms of the alloys’ electronic structure, with hybridisation between the sp states of Al and the d states of the transition metals understood to play an important role. Within our modelling, the chemically ordered B2 phases for both alloys have an increased predicted residual resistivity compared to the A2 (disordered bcc) phases. These increased resistivity values are understood to originate in a reduction in the electronic density of states at the Fermi level, in conjunction with qualitative changes to the alloys’ smeared-out Fermi surfaces. These results highlight the close connections between composition, structure, and physical properties in this technologically relevant class of materials.